Diana Lățug, "The Reception of Knut Hamsun in the Romanian Cultural Printed Press from 1895 until 2016. A National and International Perspective", București: Editura Didactică și Pedagogică, 2020, 448 p. - POP, Raluca (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Encompassing both national and international points of view, this volume is the first in-depth analysis of how Hamsun’s work was received in the Romanian cultural printed press during 1895 and 2016. The author shows progressively how Hamsun’s work was perceived by his countrymen and later on by readers in European core cultures (Russian, French, German and British) and by those in peripheral cultures such as Hungarian and former Yugoslavia. The most extensive part of the work makes use of no less than 283 articles to provide a rigorous analysis on how Hamsun’s work was received by the Romanian cultural printed press. The volume, representing Diana Lățug’s PhD thesis with the same title, was coordinated by Professor Sanda Tomescu Baciu, was publicly defended in 2017 and then published at Editura Didactică și Pedagogică in 2020.